2010
DOI: 10.1371/journal.pone.0013471
|View full text |Cite
|
Sign up to set email alerts
|

How Wealth Accumulation Can Promote Cooperation

Abstract: Explaining the emergence and stability of cooperation has been a central challenge in biology, economics and sociology. Unfortunately, the mechanisms known to promote it either require elaborate strategies or hold only under restrictive conditions. Here, we report the emergence, survival, and frequent domination of cooperation in a world characterized by selfishness and a strong temptation to defect, when individuals can accumulate wealth. In particular, we study games with local adaptation such as the prisone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Recently, Chadefaux and Helbing [26] proposed a mechanism of wealth accumulation to support cooperation. In their model wealth is created endogenously from game interactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Chadefaux and Helbing [26] proposed a mechanism of wealth accumulation to support cooperation. In their model wealth is created endogenously from game interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In many ways [26] is also the starting point of this paper. I propose a model in which agents consider differently weighted accumulated (and suitably normalized) payoffs of their opponents as the basis of decisions for strategy adoption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples range from simple microorganisms (Crespi, 2001) up to complex social interactions in society (Beinhocker, 2007). Various aspects of understanding the emergence and sustainability of such behaviour still poses a major challenge to evolutionary game theory (Weibull, 1996) and recent decades have seen very active research in the field Szolnoki et al, 2009a;Szolnoki and Szabo, 2004;Tanimoto and Yamauchi, 2010;Masuda, 2007;Abramson and Kuperman, 2001;Tanimoto and Yamauchi, 2012;Santos et al, 2006a;Zimmermann and Eguíluz, 2005;Brede, 2011b;Perc and Wang, 2010;Wang and Perc, 2010;Szolnoki et al, 2009b;Szolnoki and Szabó, 2007;Brede, 2011a;Cao et al, 2011;Zhang et al, 2010;Szolnoki et al, 2010;Szolnoki and Perc, 2008;Szabo and Hauert, 2002;Perc and Szolnoki, 2008;Santos et al, 2006b;Brede, 2013b;Van Segbroeck et al, 2009;Szolnoki et al, 2012;Chadefaux and Helbing, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that the diversity in reproduction time scales [20] and the coevolution of time scales [21] both promote cooperation. Indirect ways of altering the time scales, for example, by means of breaking the symmetry between interaction and replacement [22], wealth accumulation [23], consideration of long-term benefits [24], or other coevolutionary processes [25][26][27], have also been noted as beneficial for resolving social dilemmas. The application of a delayed distribution of accumulating goods, however, cannot be considered as a simple separation of time scales between learning (strategy adoption) and interaction (payoff accumulation) processes because cooperators, as we will see, lose their payoff permanently between two consecutive distributions, while the effective payoff of defectors remains unchanged.…”
mentioning
confidence: 99%